2009
DOI: 10.1111/j.1532-5415.2009.02383.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost Analysis of the Geriatric Resources for Assessment and Care of Elders Care Management Intervention

Abstract: OBJECTIVES To provide, from the healthcare delivery system perspective, a cost analysis of the Geriatric Resources for Assessment and Care of Elders (GRACE) intervention, which is effective in improving quality of care and outcomes. DESIGN Randomized controlled trial with physicians as the unit of randomization. SETTING Community-based primary care health centers. PARTICIPANTS Nine hundred fifty-one low-income seniors aged 65 and older; 474 participated in the intervention and 477 in usual care. INTERV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
135
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(143 citation statements)
references
References 24 publications
6
135
0
2
Order By: Relevance
“…For example, during the second year of a two-year, cluster-randomized trial, the more intensive GRACE (Geriatric Resources for Assessment and Care of Elders) model significantly reduced hospital admissions and emergency department visits (but did not affect overall health care costs) among high-risk, low-income seniors. 7,8 Similarly, recent studies of other primary care-based interventions for high-risk patients have reported significant improvement in one or two, but not all three, of the components of "the triple aim:" quality of care, health, and health care costs. 12,33 High-quality studies of various versions of the "patient-centered medical home" have shown improvement in the quality of care or in some clinical outcomes, but none has shown a significant reduction in net health care costs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, during the second year of a two-year, cluster-randomized trial, the more intensive GRACE (Geriatric Resources for Assessment and Care of Elders) model significantly reduced hospital admissions and emergency department visits (but did not affect overall health care costs) among high-risk, low-income seniors. 7,8 Similarly, recent studies of other primary care-based interventions for high-risk patients have reported significant improvement in one or two, but not all three, of the components of "the triple aim:" quality of care, health, and health care costs. 12,33 High-quality studies of various versions of the "patient-centered medical home" have shown improvement in the quality of care or in some clinical outcomes, but none has shown a significant reduction in net health care costs.…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, however, as millions of baby-boomers are reaching retirement age each year, near-term improvements may be achievable by developing and adopting clinical models that improve outcomes for high-risk people with multiple chronic conditions. Some such models have shown promise, [7][8][9][10][11][12] while others have either failed 13 or have not yet been tested rigorously. 14 Guided Care is a new model of comprehensive, interdisciplinary care that comprises primary care-based care management, transitional care, and support for self-management and family caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…3 Among the six studies meeting their evidence standards and including at least three of five PCMH characteristics while measuring triple aim, patient or professional experience outcomes, findings included only one report of significant cost savings. 4 Others reported increased costs, 5 and suggestive but inconclusive cost savings. 6,7 Half of the studies reported significant and positive reductions in hospital use, 5,8,9 while half reported suggestive but inconclusive findings.…”
Section: Introductionmentioning
confidence: 99%
“…10 A few care coordination programs have shown favorable effects, but each program was tested within a single health care system with small samples, which raises questions about the generalizability of the findings to other settings. [11][12][13] Furthermore, impacts of these programs were identified only for high-risk subsets of enrolled patients. Transitional care programs have generated major reductions in readmissions for people recently discharged from a hospital.…”
mentioning
confidence: 99%